EVALUASI KINERJA STRUKTUR DENGAN MENGGUNAKAN METODE ANALISIS PUSHOVER PADA STRUKTUR BETON BERTULANG MENGGUNAKAN APLIKASI ETABS - Muhammad Rizky Ramadhan; Ery Budiman; Mardewi Jamal (Universitas Mulawarman, 2026)
Building structures located in earthquake-prone areas must have ductile behavior and be able to withstand seismic loads safely up to a certain limit condition. This study aims to evaluate the performance of a reinforced concrete structure using the pushover analysis method with the help of ETABS software. Pushover analysis is a nonlinear static method used to determine the inelastic behavior of the structure and its performance level based on the formation of plastic hinges in the structural elements.The object of this research is a multi-story reinforced concrete building model analyzed under design earthquake loads in accordance with the provisions of SNI 1726:2019, concerning the seismic design of buildings and non-building structures. The analysis results show that plastic hinges begin to form in the beam elements before the columns, indicating that the failure mechanism follows the Strong Column-Weak Beam (SCWB) concept. Based on the performance evaluation criteria from ATC-40, the structure is categorized at the Damage Control performance level, which means that in the event of an earthquake, the building can still withstand the seismic loads with a very low risk of casualties.From these results, it can be concluded that the analyzed building structure has good performance against the design earthquake loads, and the pushover analysis method is effective in evaluating the inelastic behavior and performance level of reinforced concrete structures.